2000
DOI: 10.1046/j.1365-2702.2000.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of the nature and frequency of aggression in general ward settings and high dependency areas

Abstract: Studies on aggression in healthcare settings have reported increased frequency of this behaviour in both psychiatric and accident and emergency areas; however, to date, very few studies have addressed this issue in general ward settings in Australia. This descriptive study was conducted to determine nurses' perceptions of the nature and frequency of aggressive behaviours in general wards and high dependency areas and thereby address the gap in the literature. Two hundred and nine nurses in one Australian hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
196
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(222 citation statements)
references
References 10 publications
22
196
1
3
Order By: Relevance
“…An cak has ta ya kın la rı ta ra fın dan ge çek leş ti ri len sal dı rı la rın da ha yük sek ol du ğun -dan bah se den baş ka kül tür le re ait ça lış ma lar da bulun mak ta dır. 43,44 Jack son ve Ash ley de sö zel şid de te uğ ra ma da ka dın la rın, fi zik sel şid de te uğ ra ma da er kek le rin ora nı nın yük sek li ğin den bah set mek te dir. 5 Mes lek ola rak hem şi re ler şid de te uğ ra ma ko nu sun da da ha risk li grup tur ve bu bul gu pek çok ulus la ra ra sı yayın bul gu su ile ben zer dir.…”
Section: şId Det Son Ra Sı Baş Et Meunclassified
“…An cak has ta ya kın la rı ta ra fın dan ge çek leş ti ri len sal dı rı la rın da ha yük sek ol du ğun -dan bah se den baş ka kül tür le re ait ça lış ma lar da bulun mak ta dır. 43,44 Jack son ve Ash ley de sö zel şid de te uğ ra ma da ka dın la rın, fi zik sel şid de te uğ ra ma da er kek le rin ora nı nın yük sek li ğin den bah set mek te dir. 5 Mes lek ola rak hem şi re ler şid de te uğ ra ma ko nu sun da da ha risk li grup tur ve bu bul gu pek çok ulus la ra ra sı yayın bul gu su ile ben zer dir.…”
Section: şId Det Son Ra Sı Baş Et Meunclassified
“…In a Western Australian study that documented the prevalence of client initiated violence in general wards and high dependency settings, O'Connell, Young, Brooks, Hutchings and Lofthouse (2000) showed high levels of client initiated aggression. In this study, the researchers examined nurses' perceptions of the nature and frequency of aggression.…”
Section: Prevalencementioning
confidence: 99%
“…This study involved a random sample of 400 nurses working in one metropolitan teaching hospital. In particular, the data showed that 95% of nurses who took part in the study had encountered at least several episodes of violence in the last year, many of which were experienced in medical and surgical wards of the hospital (O'Connell et al 2000).…”
Section: Prevalencementioning
confidence: 99%
“…Various studies have shown that more than 95% of health professionals have experienced several episodes of verbal aggression in the workplace. 1 Behavioural disturbances can present in various ways, for example refusal of proposed medical intervention, wandering, self harm, depression, anxiety, agitation, threatening behaviour, aggression and violence.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that more than 95% of health professionals have experienced several episodes of verbal aggression in the workplace. 1 Behavioural disturbances can present in various ways, for example refusal of proposed medical intervention, wandering, self harm, depression, anxiety, agitation, threatening behaviour, aggression and violence.The most frequent causes of behavioural problems in hospitals are confusion, alcohol misuse, substance withdrawal, drugs, fear, physical disorder, mental disorder, traumatic brain injury, cerebral vascular accidents, Huntington's disease, dementia, unmet demands and receiving bad news.Non-pharmacological interventions should be the mainstay of managing behavioural disturbances. Indeed many can be prevented by avoiding inappropriate medications.…”
mentioning
confidence: 99%